2010
DOI: 10.1093/aje/kwq231
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature and Use of Air Conditioning on Hospitalizations

Abstract: Several investigators have documented the effect of temperature on mortality, although fewer have studied its impact on morbidity. In addition, little is known about the effectiveness of mitigation strategies such as use of air conditioners (ACs). The authors investigated the association between temperature and hospital admissions in California from 1999 to 2005. They also determined whether AC ownership and usage, assessed at the zip-code level, mitigated this association. Because of the unique spatial patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
139
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 19 publications
8
139
2
2
Order By: Relevance
“…The few studies that have investigated heat and respiratory hospitalizations have found somewhat conflicting results (6). For example, studies of Brisbane, Australia (7,8) and Athens, Greece (9) found hospitalization rates decreased slightly during hot weather, whereas studies of California (10,11), New York (12,13), and 12 European cities (14) found respiratory hospitalizations increased with heat. Although a metaanalysis of current research estimated a positive relationship between heat and respiratory hospitalizations across all studies, it lacked sufficient power to distinguish this effect from a null effect (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies that have investigated heat and respiratory hospitalizations have found somewhat conflicting results (6). For example, studies of Brisbane, Australia (7,8) and Athens, Greece (9) found hospitalization rates decreased slightly during hot weather, whereas studies of California (10,11), New York (12,13), and 12 European cities (14) found respiratory hospitalizations increased with heat. Although a metaanalysis of current research estimated a positive relationship between heat and respiratory hospitalizations across all studies, it lacked sufficient power to distinguish this effect from a null effect (6).…”
mentioning
confidence: 99%
“…U.S. studies of heat and respiratory morbidity have been limited to single cities (12,15) or single states (California [10,11,16], New York [13]) or were retrospective studies of single heat waves (17)(18)(19). Worldwide, large heterogeneity exists between temperature-morbidity studies from different locations (6,20).…”
mentioning
confidence: 99%
“…115 Ownership and use of air conditioners significantly reduced the effects of temperature on these outcomes after controlling for potential confounding by family income and other socioeconomic factors.…”
Section: Temperature Pollution and Cardiovascular Riskmentioning
confidence: 92%
“…101,[111][112][113][114] Using a case-crossover study design, California researchers observed an increased risk of hospitalization for IHD, ischemic stroke, and heat stroke with a 10°F increase in same-day apparent temperature. 115 Ownership and use of air conditioners significantly reduced the effects of temperature on these outcomes after controlling for potential confounding by family income and other socioeconomic factors.…”
Section: Temperature Pollution and Cardiovascular Riskmentioning
confidence: 92%
“…Air conditioning is known to prevent or reduce infiltration of many ambient air pollutants indoors. Individuals without air conditioning will have much greater vulnerability to aeroallergens (Delfino et al 1997) and to heat stress (IOM 2011;Ostro et al 2010;Richard et al 2011). In a recent study, vulnerability to heat waves was largely determined by socioeconomic status, including education, poverty and race; social isolation; air conditioning prevalence; and general health condition, including advanced age and diabetes (Reid et al 2009).…”
Section: Health Impacts On Changing Populations Of Susceptible and Vumentioning
confidence: 99%